Judaização da Palestina ocupada: colonização, desapropriação e deslocamento em Jerusalém Oriental, Cisjordânia e Faixa de Gaza entre 1967 e 2013 - Huberman, Bruno [UNESP] (2014)
This dissertation aims at investigating a phenomena called Judaization of Palestine: its purpose, politics, means, instruments, techniques, reasoning, objectives and interests and measure its impact on Israel-Palestine matter and lives of people living in Occupied Palestinian Territories (OPT) — palestinians and jewish settlers. In that manner, the main manifestations of this phenomenon will be historically and analitically examined, such as the development of the Jewish settlements in Palestinian territories and the legal and burocratical instruments of social control over the Palestinian population between 1967 and 2013. The central problem of this investigation is focused on the oficial arguments of the israeli authorities about the Jewish presence in the OPT and the political impasse with the palestinians, linked to the paradigm of security and conflict in opposition to the Judaization of Palestine spectrum, which is about colonization, dispossession, volunteer and involunteer desplacement and social control of a foreigner dominant social ethnical group above other indigenous and subdued one. I intend to support the judaization narrative — in opposition to the zionist hegemonic narrative — as the most appropriate to understand some of the central aspects of the dispute between israelis and palestinians over that land, as the spatial fragmentation of Cisjordani, the Gaza Strip isolation, the silent displacement occuring in East Jerusalem and the maintenance of status quo. From this we can reach the relevance and justification for the elaboration of this dissertation